What interventions are provided to help traumatized people and what was really used by them? - Tovilović, Zdravko; Ajduković, Dean; Kraljević, Radojka; Macura, Sanja Rajhvajn, Linda; Frančišković, Tanja (2007)
With the beginning of the war in Croatia a number of governmental or nongovernmental services were established, to meet the expected needs of thousands of refugees and war victims. To map the services established in the parts of Croatia and to find out what was really used by the traumatized population. We map all governmental or nongovernmental services that were providing any kind of help in 4 counties directly exposed to war. Within the randomly chosen towns using the random walking technique, we interviewed 727 persons regarding utilization of the existing services with MASCI – instrument for that purpose. 90% of interviewed persons used the primary health service, mostly during the period of war. Mental health services were used in 31, 5% cases, mostly outpatient in the same frequencies during the war and in the postwar years. The tendency of hospitalization for somatic health problems is growing by time. The least used services were social support and contact groups (4, 4%). In the parts of Croatia exposed to war official health system was the most used service and that is still the case ten years after war. The use of many newly formed, mostly NGO services, do not seem to be recognized.
Projekt MZOS
ENG